A Case-Control Study to Analyze the Association Between the Frequency of Headaches and Depression or Anxiety in Patients Suffering from Migraine - Santosh Kumar, Dileep Kumar, Ameet Kumar, Ajay Kumar, Lalchand, Hafeez Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims at investigating the presence of depression or anxiety in patients suffering from migraine. Study design: A case-control study Place and Duration: This study was conducted at Neurological Institute, Cleveland Clinic Abu Dhabi, UAE from April 2021 to April 2022 Methodology: A total of 400 participants were included in this study. The stratification of migraine was done based on the frequency of the attacks, the presence or absence of the aura, and some other significant variables. Clinical data, such as sleep characteristics, and demographic data were collected. The multivariable linear regression method was employed for the examination of the frequency of headache attacks and their association with the symptoms of anxiety and depression, as per the indication given by Hospital Anxiety and Depression Subscales (HADS) and Beck’s Depression Inventory (BDI). Results: The score of BDI was highest in the patients with chronic migraine and it was 12.9±7.8. It was 11.8±8.1 in the patients with high-frequency migraine, 10.5±7.5 in the medium frequency, 9.2±7.2 in low frequency, and 6.4±5.5 in the non-migraine participants in the control group. The trend was significant (p<0.001). The results were similar for the HADS scores. HADS and BDI scores were related independently to chronic migraine frequency, high-frequency episodic, and poor quality of sleep. A relationship between the frequency of migraine and BDI was found in both aura-absent (p=0.029) and the aura-present group (p=0.001). Conclusion: There is a significant association between a higher frequency of headaches and depression/anxiety. This relationship is important in both types of migraine; ie with aura and without aura. Keywords: depression, anxiety, migraine, headache, frequency